The Use of Weekly Quizzes in EFL Classroom - Nur Safitri S; Maemuna Muhayyang; Geminastiti Sakkir (Journal of Excellence in English Language Education, 2022)
The research aims to describe and find out the way of lecturer used weekly quizzes in EFL classroom. This research used qualitative methods. The population in this study was the lecturer and the 3rd year students of English Education Study Program in Universitas Negeri Makassar. The instrument of the research was observation. The sample for this research consists of 1 (one) lecturer of English Education Department at State University of Makassar. The result of the research found that the use of weekly quizzes in EFL classroom it can be a tool to determine and measure students' understanding of the material that has been taught previously.